The effect of hardness of sliding bodies on the wear regime transition of steels1. (20th June 2012) - Viáfara, Cristian C.; Sinatora, Amilton; Souza, Roberto M.; de, Daniel
ABSTRACT This paper aims to investigate the effect of varying the hardness of both sliding bodies on the operating wear regime. Unlubricated sliding wear tests were performed using a pin‐on‐disc configuration. The friction coefficient was monitored during the wear tests, and the variation of mass loss of bodies as a function of sliding distance was obtained to estimate the steady‐state wear rate. The results showed that the operation of mild and severe wear regimes was influenced by the initial hardness of materials. Under the high pin hardness conditions, a decrease in the disc hardness promoted the severe wear regime operation prior to the action of a mild wear regime. Under the low pin hardness conditions, a severe wear regime was established. When the harder disc was tested, a mild wear regime was observed. Copyright © 2012 John Wiley & Sons, Ltd.